ANSWER:
![\:D.\text{ }f^(-1)\left(x\right)=\left(x+4\right)^2;x\ge-4](https://img.qammunity.org/2023/formulas/mathematics/college/bwbxvy2bo6s6gzcdbrz41qy9t125xg419g.png)
Explanation:
We have the following equation:
![f(x)=√(x)-4](https://img.qammunity.org/2023/formulas/mathematics/college/mga2qoq1pvwmp26dkapy97159pe3sdt38p.png)
The inverse is the following (we calculate it by replacing f(x) by x and x by f(x)):
![\begin{gathered} x=\sqrt{f^(-1)(x)}-4 \\ \\ \sqrt{f^(-1)(x)}=x+4 \\ \\ f^(-1)(x)=(x+4)^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bs3sushkzhklsyu1eu8mdykc7lhllfa0li.png)
The domain would be the range of the original equation, and it would be the range of values that f(x) could take, which was from -4 to positive infinity, that is, f(x) ≥ -4.
Therefore, the domain is x ≥ -4.
So the correct answer is D.
![\:f^(-1)\left(x\right)=\left(x+4\right)^2;x\ge -4](https://img.qammunity.org/2023/formulas/mathematics/college/p4tyf0c6utvplj64dkmcmf6sororpj5tjl.png)